Peran E-Government Dalam Peningkatan Efesiensi Dan Efektivitas Pelayananan Publik - Tambunan, Marulitua; Dompak, Timbul (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
One of the major advances in improving the effectiveness and efficiency of public services is e-government, or electronic government. When information and communication technology is used in government, public services become more accessible, operational costs are reduced, and accountability and transparency in government management are increased. Using a literature study methodology that combines various data and conclusions from current academic sources. The purpose of this study is to assess how e-government can improve public service standards, see how it affects the effectiveness and efficiency of public services, and identify various barriers to implementation. It is hoped that this study will offer conceptual and practical insights into the importance of e-government as a tool for bureaucratic change in Indonesia. Using a literature study methodology that combines various data and conclusions from current academic sources.